Alleviation of Neuronal Cell Death and Memory Deficit with Chungkookjang Made with Bacillus amyloliquefaciens and Bacillus subtilis Potentially through Promoting Gut–Brain Axis in Artery-Occluded Gerbils - Ting Zhang; Myeong-Seon Ryu; Xuangao Wu; Hee-Jong Yang; Su Ji Jeong; Ji-Won Seo; Do-Yeon Jeong; Sunmin Park (Foods, 2021)
Short-term fermented soybeans (chungkookjang) with specific Bacillus (B.) spp. have anti-obesity, antidiabetic, and anti-stroke functions. We examined the hypothesis that the long-term consumption of B. amyloliquefaciens SCGB 1 fermented (CKJ1) and B. subtilis SCDB 291 (CKJ291) chungkookjang can alleviate clinical symptoms and hyperglycemia after ischemic stroke by promoting the gut microbiota–brain axis. We examined this hypothesis in Mongolian male gerbils with stroke symptoms induced by carotid artery occlusion. The artery-occluded gerbils were divided into five groups: no supplementation (Control, Normal-control), 4% cooked soybeans (CSB), CKJ1, or CKJ291 in a high-fat diet for 3 weeks. The carotid arteries of gerbils in the Control, CSB, CKJ1, and CKJ291 groups were occluded for 8 min and they then continued on their assigned diets for an additional 3 weeks. Normal-control gerbils had no artery occlusion. The diets in all groups contained an identical macronutrient composition using starch, casein, soybean oil, and dietary fiber. The CSB, CKJ1, and CKJ291 groups exhibited less neuronal cell death than the Control group, while the CKJ1 group produced the most significant reduction among all groups, as much as 85% of the Normal-control group. CKJ1 and CKJ291 increased the blood flow and removal of blood clots, as determined by Doppler, more than the Control. They also showed more improvement in neurological disorders from ischemic stroke. Their improvement showed a similar tendency as neuronal cell death. CKJ1 treatment improved memory impairment, measured with Y maze and passive avoidance tests, similar to the Normal-control. The gerbils in the Control group had post-stroke hyperglycemia due to decreased insulin sensitivity and β-cell function and mass; the CKJ291, CSB, and CKJ1 treatments protected against glucose disturbance after artery occlusion and were similar to the Normal-control. CKJ1 and CKJ291 also reduced serum tumor necrosis factor-α concentrations and hippocampal interleukin-1β expression levels, compared to the Control. CKJ1 and CKJ291 increased the contents of Lactobacillus, Bacillus, and Akkermansia in the cecum feces, similar to the Normal-control. Picrust2 analysis showed that CKJ1 and CKJ291 increased the propionate and butyrate metabolism and the starch and glucose metabolism but reduced the lipopolysaccharide biosynthesis and fatty acid metabolism compared to the Control. In conclusion, daily CKJ1 and CKJ291 intake prevented neuronal cell death and memory dysfunction from the artery occlusion by increasing blood flow and β-cell survival and reducing post-stroke-hyperglycemia through modulating the gut microbiome composition and metabolites to influence the host metabolism, especially inflammation and insulin resistance, protecting against neuronal cell death and brain dysfunction. CKJ1 had better effects than CKJ291.